THE INFLUENCE OF SERVICE QUALITY AND CUSTOMER VALUE ON CUSTOMER SATISFACTION AT WS HOTEL IN SURABAYA - Kevin, Kevin; Herdinata, Christian (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to examine and analyze the variables that influence customer satisfaction. The variables studied include service quality, customer value and customer satisfaction. This research is quantitative in nature and focuses on the analysis of variables that affect customer satisfaction with a survey method approach using a questionnaire. The population in this study are WS hotel customers in the period from 2021 to 2023. The research was conducted on 159 respondents using a purposive sampling technique. The results of the study show that the service quality variable has a significant and positive effect on customer satisfaction variables, the service quality variable has a significant and positive effect on customer value, the customer value variable has a significant and positive effect on customer satisfaction and the service quality variable has a significant and positive effect on satisfaction customers through customer value intervening variables. This shows that maintaining and improving service quality has an impact on customer value which in the end is expected customer satisfaction to be achieved.